Species Diversity and Gene Conservation in Indian Tree Species in Relation to forestry - Dogra, P. D. (Indian Forester, 1986)
Many widely distributed Indian forest tree species show genetic diversity. Brandis (1906) recorded intraspecifie variation to be present in some of these species. These form natural reservoirs of wild gene resources and are most valuable for plantation and tree breeding work. They must therefore be identifed and conserved to prevent extinction. Species diversity and gene conservation are therefore discussed' in this account from the point of view of Indian forestry.